The Effect of Dividend Changes on Stock and Bond Prices. - Dhillon, Upinder S; Johnson, Herb (Journal of Finance, 1994)
This study examines stock and bond price reactions to dividend changes. The positive stock market response to dividend increases has several potential explanations, two of the more commonly discussed being information content and wealth redistribution between stockholders and bondholders. The evidence presented supports the wealth redistribution hypothesis but does not rule out the information content hypothesis. Typically, the authors find that the bond price reaction to announcements of large dividend changes is opposite to the stock price reaction. Their results differ from those of G. Handjinicolaou and A. Kalay (1984).